Genetic control of root architectural traits in KDML105 chromosome segment substitution lines under well-watered and drought stress conditions. (2nd October 2021) - Ruangsiri, Mathurada; Vejchasarn, Phanchita; Saengwilai, Patompong; Lynch, Jonathan; Bennett, Malcolm J.; Brown, Kathleen M.; Chutteang, Cattleya; Boonruangrod, Ratri; Shearman, Jeremy; Toojinda, Theerayut; Siangliw, Jonaliza L.
ABSTRACT: Drought is a major constraint in rainfed rice production and root architectural traits are important breeding targets for improving productivity under drought stress. A set of chromosome segment substitution lines (KDML105-CSSLs) and KDML105 were grown in the wet season at two sites (Rice Gene Discovery (RGD) and Ubon Ratchatani Rice Research Center (URRC)) in Thailand under well-watered (WW) and drought stress (DS) treatments. RGD is characterized by having a heavy clay soil type while URRC's soil has a high percentage of sand and characterized by infertility. Root architecture traits varied within the population at both sites and exhibited plasticity in response to drought as affected by location by water regime interaction. Lateral root density increased by 77% with drought at RGD but decreased by 18% at URRC. The proportion of nodal roots that elongated more vertically increased under drought stress by 21%, at RGD. Root number per tiller was negatively associated with tiller number and biomass at RGD under drought, while lateral root density was negatively associated with biomass under drought at URRC. Eight QTL were identified for the number of nodal roots per tiller, lateral root density, and nodal root growth angle. Several candidate genes were identified by annotating the genes within the QTL regions. Our study presented genetic insights into root architectural traits with potential use in rice breeding programs for drought tolerance. Graphical abstract: uf0001